Ion Therapy: A Novel Strategy for Acute Myocardial Infarction. Issue 1 (8th November 2018) - Yi, Min; Li, Hekai; Wang, Xiaoya; Yan, Jianyun; Gao, Long; He, Yinyan; Zhong, Xinglong; Cai, Yanbin; Feng, Weijing; Wen, Zhanpeng; Wu, Chengtie; Ou, Caiwen; et al.
Abstract: Although numerous therapies are widely applied clinically and stem cells and/or biomaterial based in situ implantations have achieved some effects, few of these have observed robust myocardial regeneration. The beneficial effects on cardiac function and structure are largely acting through paracrine signaling, which preserve the border‐zone around the infarction, reduce apoptosis, blunt adverse remodeling, and promote angiogenesis. Ionic extracts from biomaterials have been proven to stimulate paracrine effects and promote cell–cell communications. Here, the paracrine stimulatory function of bioactive ions derived from biomaterials is integrated into the clinical concept of administration and proposed "ion therapy" as a novel strategy for myocardial infarction. In vitro, silicon‐ enriched ion extracts significantly increase cardiomyocyte viability and promote cell–cell communications, thus stimulating vascular formation via a paracrine effect under glucose/oxygen deprived conditions. In vivo, by intravenous injection, the bioactive silicon ions act as "diplomats" and promote crosstalk in myocardial cells, stimulate angiogenesis, and improve cardiac function post‐myocardial infarction. Abstract : "Ion therapy, " a novel strategy for treatment of acute myocardial infarction by intravenous injection of bioactive silicon (Si) ions released from silicate bioceramics, can improve cardiac function by promoting cell–cell communication, enhancing gap junction associated Cx43 expression, stimulating vascular endothelial growth factor mediated angiogenesis and blood vessel formation, and inhibiting mitogen‐activated protein kinase family protein‐associated apoptosis.